Knowledge, Skills, and Abilities for Managing Potentially Volatile Police–Public Interactions: A Narrative Review - Bennell, Craig; Jenkins, Bryce; Blaskovits, Brittany; Semple, Tori; Khanizadeh, Ariane-Jade; Brown, Andrew Steven; Jones, Natalie Jennifer (Frontiers in Psychology, 2022)
We conducted a narrative review of existing literature to identify the knowledge, skills, and abilities (KSAs) necessary for officers who police in democratic societies to successfully manage potentially volatile police–public interactions. This review revealed 10 such KSAs that are frequently discussed in the literature. These KSAs include: (1) knowledge of policies and laws; (2) an understanding of mental health-related issues; (3) an ability to interact effectively with, and show respect for, individuals from diverse community groups; (4) awareness and management of stress effects; (5) communication skills; (6) decision-making and problem-solving skills; (7) perceptual skills; (8) motor skills related to use-of-force; (9) emotion and behavior regulation; and (10) an ability to treat people in a procedurally just manner. Following our review, we conducted semi-structured interviews (N = 7) with researchers who specialize in police training and adult education, interactions with individuals in crisis, and racialized policing, as well as two police trainers with expertise in de-escalation and use-of-force training. These interviews confirmed the importance of the 10 KSAs and highlighted two additional KSAs that are likely to be critical: understanding the role of policing in a free and democratic society and tactical knowledge and skills. To ensure that police–public interactions are managed effectively, police trainers may want to focus on the development and evaluation of these KSAs—something that is not always done currently.